Born to die [large type] - Jackson, Lisa (Jackson, Lisa. Selena Alvarez/Regan Pescoli novels., 2011)
After the mysterious deaths of two women who bear an uncanny resemblance to Dr. Kacey Lambert, Detective Selena Alvarez suspects murder. Kacey fears she may be the next victim when she starts to notice connections between herself and the dead women.